Welcome to Freshwater Systems, A Domain of TheScientificWorld - Karl E. Havens; Lorraine Maltby; Karl K. Ramesh Reddy (The Scientific World Journal)
With an ever-increasing human population size, increasing human impacts on the natural environment, and a growing scarcity of freshwater resources, the study of freshwater systems has become one of the most critical areas of focus for environmental scientists. Never before has there been such a need for an integrated understanding of lakes, wetlands, and flowing waters. This understanding must cross the boundaries of traditional disciplines, reach a wide international audience, and strongly facilitate the linkage between scientific discovery and its real-world application.